A new sulphated flavone and other phytoconstituents from the leaves of Tetracera indica Merr. and their alpha-glucosidase inhibitory activity - Alhassan, Alhassan Muhammad; Ahmed, Qamar Uddin; Latip, Jalifah; Shah, Syed Adnan Ali (Taylor and Francis, 2019)
The bioactivity guided fractionation of Tetracera indica leaves crude ethanolic extract has afforded the isolation and characterization of six compounds including a new natural product viz., 5,7-dihydroxyflavone-O-8-sulphate (1) and five known flavonoids (2–6). The structures of the compounds were elucidated using 1D and 2D NMR and HRESIMS spectroscopic analyses. All the isolated compounds were evaluated for their in vitro inhibitory activity against alpha-glucosidase. Compound 1, 5 and 6 showed strong alpha-glucosidase inhibitory activity, 3 and 4 displayed weak activity while compound 2 was inactive. The interactions of the active compounds with alpha-glucosidase were further investigated using molecular docking to confirm their antidiabetic potential.